Aspek Gender Equality (Keadilan Gender) Bagi Korban dalam Undang – Undang Nomor 12 Tahun 2022 Tentang Tindak Pidana Kekerasan Seksual - Zainur Ratna Savitri; Riza Nisriinaa; Dominikus Rato; Fendi Setyawan (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Victims of sexual harashment are often associated with vulnerable groups, namely women, children, people with disabilities and elderly people, even though groups that are not vulnerable are men who have relatively stronger physical strength than women, have better self-defense abilities, turns out to also be a victim, it means that anyone can become a victim of sexual violence. However, it turns out that there is no certainty and legal protection for all forms of gender justice for victims of sexual violence. Therefore, it is important to have and at the same time strive for legal protection in abstracto in a regulation that specifically accommodates gender justice for victims of sexual violence. Has the enactment of Law Number 12 of 2022 concerning Crimes of Sexual Violence accommodated aspects of gender justice in providing legal protection for victims of sexual violence and how is the punishment in Law Number 12 of 2022 concerning Crimes of Sexual Violence to realize gender justice for victims of sexual violence, considering Imposing criminal sanctions on perpetrators is a form of legal protection in concreto for victims, so that they have the same access to justice as humans without any gender bias in the implementation of law enforcement.